2002
DOI: 10.1016/s0370-2693(02)01337-0
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing branes

Abstract: Two classical scalar fields are minimally coupled to gravity in the Kachru-Shulz-Silverstein scenario with a rolling fifth radius. A Tolman wormhole solution is found for a IR×S 3 brane with Lorentz metric and for a IR × AdS 3 brane with positive definite metric.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The same picture can be found in [85] where the non-minimal coupling of gravity to fermions is allowed. Besides the model presented here, non-singular scenarios have been reported in the literature within various models such as f (R) theories of gravity in the Palatini [86] and metric [87] formalisms, nonsingular cosmological settings in the presence of a spinning fluid in the context of EC theory [88], bouncing scenarios in brane models [89][90][91][92][93], and modified Gauss-Bonnet gravity [94] (see also [95] for recent review). While the spacetime singularities could generically occur as the end-product of a continual gravitational collapse, it is widely believed that in the very final stages of the collapse where the scales are comparable to the Planck length and extreme gravity regions are dominant, quantum corrections could generate a strong negative pressure in the interior of the cloud to finally resolve the classical singularity [96][97][98][99][100][101][102][103][104][105][106][107].…”
Section: Discussionmentioning
confidence: 99%
“…The same picture can be found in [85] where the non-minimal coupling of gravity to fermions is allowed. Besides the model presented here, non-singular scenarios have been reported in the literature within various models such as f (R) theories of gravity in the Palatini [86] and metric [87] formalisms, nonsingular cosmological settings in the presence of a spinning fluid in the context of EC theory [88], bouncing scenarios in brane models [89][90][91][92][93], and modified Gauss-Bonnet gravity [94] (see also [95] for recent review). While the spacetime singularities could generically occur as the end-product of a continual gravitational collapse, it is widely believed that in the very final stages of the collapse where the scales are comparable to the Planck length and extreme gravity regions are dominant, quantum corrections could generate a strong negative pressure in the interior of the cloud to finally resolve the classical singularity [96][97][98][99][100][101][102][103][104][105][106][107].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that, besides the model presented here, non-singular scenarios have been reported within models of f (R) theories of gravity in Palatini [171] and metric [172] formalisms, generalized teleparallel theories of gravity [173][174][175][176], bouncing in brane models [177][178][179][180][181] and modified Gauss-Bonnet gravity [182] (see also [183] for recent review). In [184], it is shown that a quantized neutral scalar field minimally coupled to classical gravitational field may avoid the singularity.…”
Section: Discussionmentioning
confidence: 74%
“…Brane-world models permit a new approach to these difficulties, since they appear to allow the possibility that brane-bound observers might experience a bouncing universe, while embedded within a stable higher-dimensional geometry [3,4,5,6,7,8,9,10,11,12,13]. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Brane-world models permit a new approach to these difficulties, since they appear to allow the possibility that brane-bound observers might experience a bouncing universe, while embedded within a stable higher-dimensional geometry [3]- [16]. Reference [8] pointed out such an apparent example, consisting of a four-dimensional cosmology based on a brane world embedded in a five-dimensional Reissner-Nordström background 6 .…”
Section: Introductionmentioning
confidence: 99%